Dysmetric Eye Movements in Tourette Syndrome - J Gordon Millichap (Pediatric Neurology Briefs)
A 13-year-old boy with an 11 year history of Tourette syndrome and progressively worsening tics, both motor and vocal, was referred to the Department of Ophthalmology, Great Ormond Street Hospital, London, because of visual symptoms and reading problems.